Evaluation of color stability of different temporary restorative materials - Mazaro, José Vitor Quinelli; Minani, Luiz Miguel; Zavanelli, Adriana Cristina; Mello, Caroline Cantieri De; Lemos, Cleidiel Aparecido Araújo (Universidade Estadual Paulista Júlio de Mesquita Filho, 2015)
AbstractIntroductionTemporary restorative materials are widely used, however, little is know about their color stability.Objectiveto evaluate the color stability of the following temporary restorative materials: acrylic and bis-acrylic resins after immersion in pigmenting solutions for different periods of storage.Material and methodFour materials were tested (Dêncor/Clássico, Protemp 4/3M ESPE; Structur 2 SC/Voco; Luxatemp AM Plus/DMG) and 30 test specimens (15 mm in diameter and 2 mm thick) per material were fabricated. They were divided according to the storage medium (artificial saliva, saliva + cola type soda, and saliva + coffee) and storage time intervals (2, 5, 7 and 15 days). Color measurements were made before and after immersions, with use of a spectrophotometer, by means of the CIE L*a*b* system. The data were analyzed by the analysis of variance and the Tukey Test, at a level of significance of 5%.ResultAcrylic resin presented greater color stability in comparison with bis-acrylic resins (p<0.001). When bis-acrylic resins were compared no significant difference was observed between the resins Structur and Luxatemp (p=0.767). As regards solutions tested, coffee showed the highest color change values (p<0.001), and the longer the storage time interval, the greater was the color change in all the temporary restorative materials analyzed (p<0.001).ConclusionAcrylic resin presented greater color stability in comparison with bis-acrylic resins (p<0.001). Coffee caused the greatest color change, and immersion time was determinant in color stability of the temporary materials analyzed.

ResumoIntroduçãoOs materiais restauradores provisórios são amplamente utilizados, porém pouco se sabe a respeito de sua estabilidade de cor.ObjetivoAvaliar a estabilidade de cor de materiais restauradores provisórios: resina acrílica e resinas bisacrílicas, após a imersão em soluções pigmentantes, durante diferentes períodos de armazenamento.Material e métodoQuatro materiais foram testados (Dêncor/Clássico, Protemp 4/3M ESPE; Structur 2 SC/Voco; Luxatemp AM Plus/DMG) sendo confeccionadas 30 amostras (15 mm de diâmetro e 2 mm de espessura) por material. Estes foram divididos de acordo com o meio de imersão (saliva artificial, saliva + refrigerante tipo cola e saliva + café) e período de armazenamento (2, 5, 7 e 15 dias). As mensurações de cor foram realizadas antes e após as imersões, com auxílio de um espectrofotômetro, através do sistema CIE L*a*b*. Os dados foram analisados com análise de variância (ANOVA) e Tukey, com nível de significância à 5%.ResultadoA resina acrílica apresentou maior estabilidade de cor quando comparada às resinas bisacrílicas (p<0,001). Comparando as resinas bisacrílicas, não foi observado diferença significativa entre as resinas Structur e Luxatemp (p=0,767). Em relação as soluções testadas, o café apresentou os maiores valores de alteração de cor (p<0,001), sendo que quanto maior o período de armazenamento, maior foi a alteração de cor de todos os materiais provisórios analisados (p<0,001).ConclusãoA resina acrílica apresentou maior estabilidade de cor, quando comparada às bisacrílicas. O café causou a maior alteração de cor, e o tempo de imersão foi determinante na estabilidade de cor dos materiais provisórios analisados.
Avaliação da estabilidade de cor de diferentes materiais restauradores provisórios
Keywords: Dental restoration temporary; color; dental prosthesis; Restauração dentária temporária; cor; prótese dentária